Equalizer sharing in wireless communications: Simulation study - Mohd Fadzil, Ain; Mutamed, Khatib; Syed Idris, Syed Hassan; Farid, Ghani (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/